2021
DOI: 10.1155/2021/7484812
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Parotid Gland Tuberculosis

Abstract: Parotid gland tuberculosis is a very rare form of extrapulmonary tuberculosis, with less than 200 cases reported in literature. We describe a 10-year-old female who presented with a swelling in the left parotid region during the last month. CT scan neck revealed an abscess in the left parotid gland extending into the submandibular gland, muscles, and bone. Pus aspirated by FNAC showed acid fast bacilli in the ZN stain, and GeneXpert was positive for rifampicin-sensitive Mycobacterium tuberculosis. She was succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Additionally, another retrospective study conducted at a rural tertiary care hospital further emphasized the rarity of parotid abscesses, noting that methicillin-susceptible Staphylococcus aureus was the most common pathogen and poor dental hygiene was the most important predisposing risk factor [10]. Isolated case reports note that tuberculosis is a possible cause of parotid abscesses that do not respond to antibiotic therapy [11,12]. However, the patient in this case did not display signs or symptoms of infection, including fever and general malaise.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, another retrospective study conducted at a rural tertiary care hospital further emphasized the rarity of parotid abscesses, noting that methicillin-susceptible Staphylococcus aureus was the most common pathogen and poor dental hygiene was the most important predisposing risk factor [10]. Isolated case reports note that tuberculosis is a possible cause of parotid abscesses that do not respond to antibiotic therapy [11,12]. However, the patient in this case did not display signs or symptoms of infection, including fever and general malaise.…”
Section: Discussionmentioning
confidence: 85%
“…Tuberculosis of salivary glands is very rare and that of the parotid glands is the rarest of rare clinical presentations [6]. Further, rifampicin mono-resistance has never been reported in parotid glands.…”
Section: Discussionmentioning
confidence: 99%
“…Birkent et al in 2008 reported that it requires a very high index of suspicion, especially in the absence of any symptoms of tuberculosis or any history of contact [4]. The rarity of this clinical entity could result in missed diagnosis and superfluous parotidectomies [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation